2011
DOI: 10.1007/s00330-011-2104-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CT-colonography as compared to colonoscopy in an asymptomatic screening population: a meta-analysis

Abstract: ObjectivesPrevious meta-analyses on CT-colonography included both average and high risk individuals, which may overestimate the diagnostic value in screening. A meta-analysis was performed to obtain the value of CT-colonography for screening.MethodsA search was performed using PubMed, Embase and Cochrane. Article selection and critical appraisal was done by two reviewers. Inclusion criteria: prospective, randomized trials or cohort studies comparing CT-colonography with colonoscopy (≥50 participants), ≥95% ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 32 publications
2
84
1
9
Order By: Relevance
“…Sensitivität und Spezifität der CT-Kolonografie sind in den letzten Jahren seit Erstellung der letzten Leitlinie angestiegen. In Übersichten der letzten Jahre lag die CT-Kolonografie entweder um 10 -20 % zurück (größen-abhängig) für alle Neoplasien im Screening-Setting [173], erreichte eine gute (88 %) Treffsicherheit für Adenome > 5 mm bei Stuhltest-positiven Screening-Kandidaten bei allerdings nur 75 % Spezifität [435], und zeigte eine sehr hohe Treffsicherheit für Karzinome in einer radiologischen Übersicht bei allen Indikationen [412]. Was die Patientenpräferenz für CT vs. Koloskopie betrifft, hängen die Ergebnisse offenbar vorwiegend vom Journal der Veröffentlichung (Radiologie vs. Gastroenterologie/Innere) und vom Ausmaß der Darmvorbereitung beim CT ab [436].…”
Section: Level Of Evidence 1cunclassified
“…Sensitivität und Spezifität der CT-Kolonografie sind in den letzten Jahren seit Erstellung der letzten Leitlinie angestiegen. In Übersichten der letzten Jahre lag die CT-Kolonografie entweder um 10 -20 % zurück (größen-abhängig) für alle Neoplasien im Screening-Setting [173], erreichte eine gute (88 %) Treffsicherheit für Adenome > 5 mm bei Stuhltest-positiven Screening-Kandidaten bei allerdings nur 75 % Spezifität [435], und zeigte eine sehr hohe Treffsicherheit für Karzinome in einer radiologischen Übersicht bei allen Indikationen [412]. Was die Patientenpräferenz für CT vs. Koloskopie betrifft, hängen die Ergebnisse offenbar vorwiegend vom Journal der Veröffentlichung (Radiologie vs. Gastroenterologie/Innere) und vom Ausmaß der Darmvorbereitung beim CT ab [436].…”
Section: Level Of Evidence 1cunclassified
“…31 Table 1 provides an overview of the lesion-specific test characteristics for all evaluated screening tests. Test characteristics were based on meta-analyses on CTC, 16,17,33 screening trials and a meta-analysis on MRC [18][19][20][21] and a systematic review on colonoscopy. 34 Because the literature does not provide lesion-specific FIT sensitivities, these were estimated via calibration of the model-predicted FIT positivity and detection rates for advanced adenomas and CRC to figures reported for a Dutch FIT screening trial.…”
Section: Screening Strategiesmentioning
confidence: 99%
“…6 for detecting small adenomas is slightly lower than that of colonoscopy, [13][14][15] whereas the sensitivity for detecting large adenomas and CRC is comparable. 16,17 MRC, which in contrast to CTC is free from ionizing radiation, is evaluated in a limited number of studies only. These studies showed that MRC has a lower sensitivity for small and large adenomas than colonoscopy but has a similar sensitivity for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Perpatient analyses demonstrated a sensitivity of 78.0% to 93.8%, and specificity of 79.6% to 96.0%, respectively. 47,48 Meta-analyses in 2011 and 2014 reviewed 15 trials, 49,50 including the two aforementioned studies. All trials focused on a population aged over 50 years with average risk.…”
Section: Computed Tomographic Colonographymentioning
confidence: 99%
“…Another meta-analysis reported sensitivities for ≥6-mm and ≥10-mm polyps as 75.9% and 83.3% and specificities as 94.6% and 98.7%, respectively. 50 Estimation of the cost-effectiveness remains complicated. Based on a systematic review of 16 studies, 51 the cost-effectiveness of CTC remains controversial.…”
Section: Computed Tomographic Colonographymentioning
confidence: 99%